Developing Students’ Vocabulary by Using Magic Boxgame at SMPN 8 Palopo - Sarhang, Riri Yanti; Furwana, Dewi (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research about Developing Students’ Vocabulary by Using Magic Box Game at the Eighth-grade of SMPN 8 Palopo. The research question of this research was Does The Use of Magic Box Game Develop Students’ English Vocabulary at SMPN 8 Palopo. The objective of this research was to find out whether or not the use of magic box games can develop students’ English vocabulary. This research applied quasi-experimental. The population of this research was the eighth-grade students of SMPN 8 Palopo. The population was 283 students. the sample was class VIII 2 consisted of 30 students as an experimental group and class VIII 9 consisted of 30 students as the control group. The sampling technique in this research was purposive sampling. The instrument of the research was a vocabulary test. The researcher gave pretest and posttest to the students. As a result, there was a significant difference in vocabulary achievement between the students who are taught by using magic box game and those who are taught by non using magic box game. Based on the result of this research, the researcher concluded that the magic box game develops the students’ vocabulary.